Effect of Village Financial Report Presentation, Internal Control, Individual Morality, and Competence on Fraud Prevention in Village Fund Allocation Management - Putri Febriana; Sarwenda Biduri (Indonesian Journal of Cultural and Community Development, 2022)
This study aims to analyze the influence of village financial statements presentation, internal control, individual morality, and competence on fraud prevention in managing village fund allocation (study of villages in Sidoarjo district). The sampling method used is a saturated sampling technique because the population is relatively small. The sample in this study were 76 respondents. Each village is represented by 4 people, namely the Village Head, Village Secretary, Village Treasurer, and BPD in Tanggulangin District, Sidoarjo Regency, namely 19 villages including the villages of Banjar Asri, Banjar Panji, Boro, Ganggang Panjang, Gempol Sari, Kalidawir, Kalisampurno, Kalitengah, Kedensari, Kedung Banteng, Kedung Bendo, Ketapang, Ketegan, Kludan, Ngaban, Penatarsewu, Putat, Randegan, and Sentul. The data used is primary data. The data analysis method used in this study is Multiple Linear Regression with SPSS 25. The results of this study indicate that the Presentation of Village Financial Statements Affects Fraud Prevention in Village Fund Allocation Management. Internal Control Affects Fraud Prevention in the Management of Village Fund Allocation. Individual Morale Affects Fraud Prevention in the Management of Village Fund Allocation. Competence Affects Fraud Prevention in Village Fund Allocation Management.